Memory, identity and unspeakability in trauma narration of selected novels by Tash Aw and Tan Twan Eng - Hou, Xia (2023)
The literary canon of trauma novels has focused chiefly on the characters’ psychological, cultural, and postcolonial contexts. However, more research is required on narrative ways to represent traumatic memory, identity, and reconstruction of identity through modes of narration. Contemporary Chinese Malaysian novelists Tash Aw and Tan Twan Eng portray the psychological states of minority communities, especially Chinese Malayans, during the colonial period from the 1940s to the 1960s. Past research on Tash Aw and Tan Twan Eng’s works has mainly focused on aspects such as transculturation, colonial concepts of identity, and aestheticism of memory. Herein, my thesis attempts to fill in the gap by examining how trauma is represented by narrative techniques in selected texts and how narration plays an integral role in negotiating trauma. My central argument is that narration plays a crucial role in representing and healing trauma in Tash Aw and Tan Twan Eng’s novels. Cathy Caruth’s conception of trauma indicates the symptoms as belatedness and repetition of intrusive memories. Toolan’s time and space are conducive to representing such nonlinear and circular sequences caused by trauma. Cathy Caruth’s expression of “blow to the mind” results in a dissociative identity that is embodied by extreme long-lasting emotions, such as numbness, rage, depression, loss, and helplessness. Toolan’s internal focalization and Hogan’s affective narration are useful to show the change of emotions reflecting the state of identity. Cathy Caruth’s “collapse of understanding” leading to further research on Anne Whitehead’s “absence of narrative capacity” will be applied as a way to understand protagonists’ unspeakability in the selected novels. Anne Whitehead’s conversion of traumatic memory into narrative memory represents the process of recovery from trauma. Astril Erll’s modes of whole- text narration will be used to analyze the specific healing process. I analyze Tash Aw’s The Harmony Silk Factory (2005), Map of the Invisible World (2009) and Tan Twan Eng’s The Gift of Rain (2007) and The Garden of Evening Mists (2012) to show how these works demonstrate trauma symptoms through narrative arrangement